(untitled) (Revista Rupturas, 2016)
This paper analyzes the relationship between the situation in the migratory system between the United States and Tarrazú and social representations of migrants, in the light of the changes caused by factors such as: the resurgence of US immigration policy, World Economic Crisis, and the construction of Hydroelectric project Pirrís. The central argument is based on the analysis of the life stories of migrants and the social representations present in their discursive productions, in that sense, concepts like symbolic capital and migratory social networks are central to understanding the change of ideas that have emerged in the context of transformations.